Investigation of OTDM Demultiplexing and Hybrid Techniques - Lata, Sneh (My University, 2014)
Optical fiber communication provides transmission of light and thus information over long distances. Optical fibers offer huge data transmission capacity. There are several multiplexing techniques used for optical fiber communication including FDM (frequency division multiplexing), TDM (Time Division Multiplexing) and WDM (Wavelength Division Multiplexing). OTDM (Optical Time Division Multiplexing) is a powerful multiplexing technique that provides very high capacity of data transmission over optical fibers. In OTDM networks, several lower bit-rate optical streams are time-multiplexed to generate a high bit-rate data stream. Likewise, at the receiver side of the system, the high bit-rate optical signal is time demultiplexed to several lower bit-rate signals. The most critical element of the OTDM system is the demultiplexer. So far, different demultiplexing schemes have been proposed for the demultiplexing of OTDM signals including various optical gate switches and other methods. A good demultiplexer design is essential for receiving error-free signal with efficient bit error rate (BER) performance and to decrease the cross-talk between the channels. One method for achieving the efficient demultiplexing system is to use optical gating using different types of modulators arranged in different configurations. Efficient demultiplexing can also be attained by utilizing hybrid OTDM system. Using hybrid OTDM networks helps in reducing the crosstalk between the adjacent channels thereby improving the overall system performance. The main objective of this dissertation is to investigate and propose OTDM demultiplexing and hybrid architectures for enhanced and error-free performance. Firstly, 160 Gb/s OTDM DQPSK system with optical gating using mach-zehnder modulator and clock recovery is analyzed. Secondly, serial-to-parallel conversion of optical time division multiplexed (OTDM) data tributaries into wavelength division multiplexed (WDM) channels from 160 Gbit/s to 4x40 Gbit/s using four-wave mixing (FWM) in highly non-linear fiber (HNLF) followed by a single electro-absorption modulator based optical gate. Thirdly, a 160 Gb/s hybrid optical time-division multiplexing (OTDM) system is demonstrated which contains hybrid modulation formats of on-off keying (OOK) and differential phase shift keying (DPSK) and its demultiplexing performance is investigated using a mach-zehnder modulator
ME, ECED
Keywords: OTDM, OOK; DPSK, WDM